"Staying at Home": A pivotal trial of telemedicine-based internal medicine hospitalization at a nursing home. (September 2022) - Barkai, G; Amir, H; Dulberg, O.; Itelman, E; Gez, G; Carmon, T; Merhav, L; Zigler, S; Atamne, A; Pinhasov, O; Zimlichman, E; Segal, G
Background: In-hospital stay of acutely ill elderlies could be reduced by increasing the availability of community-based hospitalizations. The feasibility of remotely managing these patients by specialized internists, without leaving their nursing homes should be sought. In the current pivotal study, we aimed to evaluate the aforementioned model. Methods: This was a prospective, open-label study at a tertiary medical center and a nursing home. The study aimed at comparing clinical outcomes of patients hospitalized in each location. Results: Over a period of 5.5 months, we recruited 18 patients designated for hospitalization, meeting our inclusion criteria to either in-hospital stay or staying in their nursing home and treated by means of telemedicine from our tertiary medical center. The mean age was 85.3 years. Out of 114 hospitalization days, 44 days (48%) were at the nursing home. No significant difference was noted in terms of age, gender, and length of stay between the patients who were hospitalized in either location. In almost all cases, diagnosis changed during hospitalization. Three patients died during the study, all included in the in-hospital group. No safety breaching events happened in the nursing home-hospitalization group. Conclusions: Remote, telemedicine-based hospitalization of nursing home-dwelling elderlies is safe and feasible, potentially reducing the length of in-hospital stay by almost 50%. Larger studies in this realm are warranted.